2013
DOI: 10.2224/sbp.2013.41.10.1625
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Fear of Contagion as Factors in Aggressive Tendency of Health-Care Workers Treating People with Aids

Abstract: We investigated the roles of burnout and perceived fear of contagion with AIDS among 130 medical practitioners and 112 nurses (N = 242) working in AIDS care in Nigeria, in relation to the level of their aggressive tendency toward people living with AIDS (PLWAs). Participants completed scales concerning perceived AIDS anxiety, burnout, and aggressive tendency. Results showed that perceived fear of AIDS, burnout, and category of staff (medical practitioner or nurse), respectively, were associated with the tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The majority of studies assessed burnout using the MBI. Among those that used the MBI, burnout scores were variously reported as (1) percentage of participants with high burnout on each subscale [58, 72, 81, 87, 99, 106, 116], (2) percentage of participants with high burnout on each subscale and total score [55, 66, 101] (3) percentage of participants with high total burnout [91, 105], (4) percentage of participants with high burnout on emotional exhaustion subscale only [71], (5) total and individual burnout as a continuous scores [59], (6) total burnout as continuous score [69, 78, 110], (7) individual burnout as continuous score [60, 64, 70, 73, 75, 76, 82, 88, 90, 104, 108, 109, 112, 115, 117], or (8) both individual burnout as continuous sores and percentages of participants with high burnout [56, 57, 61, 77, 96]. Furthermore, included studies used four different versions of the MBI to assess burnout including the MBI, MBI-HSS, Abbreviated MBI, and MBI-GS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies assessed burnout using the MBI. Among those that used the MBI, burnout scores were variously reported as (1) percentage of participants with high burnout on each subscale [58, 72, 81, 87, 99, 106, 116], (2) percentage of participants with high burnout on each subscale and total score [55, 66, 101] (3) percentage of participants with high total burnout [91, 105], (4) percentage of participants with high burnout on emotional exhaustion subscale only [71], (5) total and individual burnout as a continuous scores [59], (6) total burnout as continuous score [69, 78, 110], (7) individual burnout as continuous score [60, 64, 70, 73, 75, 76, 82, 88, 90, 104, 108, 109, 112, 115, 117], or (8) both individual burnout as continuous sores and percentages of participants with high burnout [56, 57, 61, 77, 96]. Furthermore, included studies used four different versions of the MBI to assess burnout including the MBI, MBI-HSS, Abbreviated MBI, and MBI-GS.…”
Section: Discussionmentioning
confidence: 99%
“…Depersonalization was significantly associated with heavy workload ( p = 0.034). Reduced personal accomplishment was associated with younger age ( p = 0.03).Nel, 2013 [109]South AfricaHealthcare workers at public and private hospitals ( N = 511)MBI-HSSEmotional exhaustion (mean ± SD): 15.2 ± 7.2Mental distance: 13.6 ± 9.3The proposed structural model shows paths between job demands and job resources; job demands, emotional intelligence and work wellness; job resources, emotional intelligence and work wellness.Ojedokun, 2013 [110]NigeriaHealthcare workers working in AIDs care ( N = 242)MBI66.4 ± 21.5 (mean ± SD)Burnout was significantly associated with aggressive tendency and perceived fear of AIDS ( p < 0.01)Olley, 2003 [111]NigeriaHealthcare workers at a teaching hospital ( N = 260)MBINot reportedNurses reported higher scores on burnout subscales compared to other healthcare providers ( p < 0.05). Significant differences were found between nurses and other healthcare providers on the General Health Questionnaire-12 ( p < 0.01) and the State Trait Anxiety Inventory ( p < 0.05).Thorsen, 2011 [112]MalawiHealthcare workers in a referral hospital ( N = 101)MBI-HSSEmotional exhaustion (mean ± SD): 23.1 ± 9.7Depersonalization: 6.2 ± 4.8Personal accomplishment: 37.8 ± 7.5Sociodemographic characteristics were not associated with the emotional exhaustion subscale of burnout.…”
Section: Methodsmentioning
confidence: 99%
“…Collectively, this suggests coworker presenteeism may correspond with greater fear of contagion when an individual is more demographically similar to his or her coworkers. Because fear of contagion presents a direct threat to one’s own well-being, it is a stressor that leads to negative emotions, as evidenced by medical literature about nurses caring for patients with actual or perceived contagious diseases (e.g., Ojedokun, Idemudia, & Kute, 2013).…”
Section: Studymentioning
confidence: 99%
“…Collectively, this suggests coworker presenteeism may correspond with greater fear of contagion when an individual is more demographically similar to his or her coworkers. Because fear of contagion presents a direct threat to one's own well-being, it is a stressor that leads to negative emotions, as evidenced by medical literature about nurses caring for patients with actual or perceived contagious diseases (e.g., Ojedokun, Idemudia, & Kute, 2013). Such emotionally rich responses encompass a plethora of both positive and negative affect and, as such, are apt to result in favorable or unfavorable behavioral reactions, respectively (Weiss, Suckow, & Cropanzano, 1999).…”
Section: Fear Of Contagionmentioning
confidence: 99%
“…Structural conditions, including poor working conditions and inadequate staff and resources, inevitably play their part (Pires, d'Oliveira, Diniz, & Schraiber, 2002). However, it has also been suggested that these factors are important not so much in themselves, but in the conditions they engender, producing exhaustion and diminished capacity for empathy (Ojedokun, Idemudia, & Kute, 2013;Reader, Gillespie, & Minnelli, 2014). With reference to South African public sector services, Jewkes, Abrahams, and Mvo (1998) argue that structural conditions encourage lack of accountability (Jewkes et al, 1998), at the same time enhancing the difficulty of ethical decisions (Baldwin-Ragaven, de Gruchy, & London, 1999;Gibson, 2004).…”
Section: Introductionmentioning
confidence: 99%